Elenchus, Intellectualism, and Shame in Plato’s Gorgias - Bieda, Esteban (Revista Archai, 2025)
In this paper I intend to underline an aspect of the socratic elenchos that we call “practical approach”. Within this framework I emphasize the relationship between Socratic refutation and the situation and emotions involved in it, as it is well testified in Plato’s Gorgias, where the conversation takes place in public. Our approach also reveals itself as being “practical” since it has, as I try to show, a very close link to the so called “Socratic Intellectualism” (SI). In the Gorgias, even if a case in which a decision contrary to what the agent considers better for himself is made can be found, this situation does not constitute a counterexample for the SI, insofar as what is important at the moment of making decisions is not just the opinions the agent has at a propositional level, but also the shame that could be involved in case some specific answer is given in front of an audience. Thus, our conclusion is that the Socratic theory of action is closely related to the elenchos since the latter involves not only the epistemic opinions of the agent but also his existencial condition linked to the presence of other people.